2021
DOI: 10.14324/rfa.05.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond the one-off: How can STEM engagement programmes with young people have real lasting impact?

Abstract: A major focus in the science, technology, engineering and mathematics (STEM) public engagement sector concerns engaging with young people, typically through schools. The aims of these interventions are often to positively affect students’ aspirations towards continuing STEM education and ultimately into STEM-related careers. Most school engagement activities take the form of short one-off interventions that, while able to achieve positive outcomes, are limited in the extent to which they can have lasting impac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Parental engagement is notoriously difficult within school-based programmes in general (see the review of M. O. Archer et al, 2021), so we simply aim to include parents/carers to celebrate in students' project work at the end of the programme. These parents/carers are likely interested in their children's education.…”
Section: Keymentioning
confidence: 99%
“…Parental engagement is notoriously difficult within school-based programmes in general (see the review of M. O. Archer et al, 2021), so we simply aim to include parents/carers to celebrate in students' project work at the end of the programme. These parents/carers are likely interested in their children's education.…”
Section: Keymentioning
confidence: 99%
“…Independent research projects and "research in schools", when appropriately developed and supported by expert mentors from universities or industry, thus potentially align with this direction. Bennett et al (2016Bennett et al ( , 2018 reviewed the evidence of impact from independent research project endeavours globally. They found that impacts on students were most often investigated, with various outcomes being reported including improved understanding, practical and transferable skills, or attitudes and aspirations towards science.…”
Section: Introductionmentioning
confidence: 99%
“…Dunlop et al (2019) further suggest there is value in students participating in independent research projects through developing their understanding about scientific research/researchers and allowing them to make more informed decisions about their future subject choices. It appears at present though that only a few programmes consider the impact on students from underrepresented groups, presenting emerging evidence that increased engagement with science can result from their involvement (Bennett et al, 2016(Bennett et al, , 2018. Finally, the review highlights that evaluations exploring the potential long-term impacts of project work on students, such as subsequent subject or career choices, are currently lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations